Quantum Surface Topological Code for Bell State Stabilization in Superconducting Physical Qubit Systems - Jordi Fabián González-Contreras; Erik Zamora; Jesús Yaljá Montiel-Pérez; Juan Humberto Sossa-Azuela; Elsa Rubio-Espino; Víctor Hugo Ponce-Ponce (Mathematics)
Stabilizing quantum states in physical qubits quantum computers has been a widely explored topic in the Noisy Intermediate-Scale Quantum era. However, much of this work has focused on simulation rather than practical implementation. In this study, an experimental advancement in Bell state stabilization is presented, which utilizes surface codes for quantum error correction across three quantum computers: ibm_fez, ibm_torino, and ibm_brisbane. Our findings indicate that error correction produces an improvement of approximately 3% in accuracy for 127-qubit systems while demonstrating a more significant enhancement of around 20% for 156-qubit systems in stabilizing the Bell state with fidelity up to 0.6 in all the experiments. This paper outlines the methodology for implementing this strategy in other applications, offering a pathway to improve results (<semantics>≈20%</semantics>) when experimenting with superconducting quantum computers.